(untitled) (EAAE Joint Publishings, 2026)
Digital tools have become a part of most architectural education worldwide. Today, digital tools include much more than just drawing and modeling software. Every aspect of architectural design and development is digitized, and the component and construction industries are increasingly implementing digitization and automation. As such, digital knowledge and literacy in and around the architectural process are vast and constantly changing. While architectural education can include courses and implementations of certain digital tools, it seems impossible to teach all aspects of digital possibilities within the limited timespan of academic education. A strategy and didactic approach to the digital tool can guide the position of the educational institution and structure the ambition and intention of how digital competencies are brought to the students. Focused work on the digital curriculum at Aarhus School of Architecture led to a framework for digital teaching throughout the bachelor’s and master’s programs. A series of material- and research-based workshops for 2nd-year students were developed within that framework. This paper discusses the content of these specific hands-on digital courses regarding their intention and ambition as components in architectural education